An Analysis of al-Kindi and John of Damascus’s Argument and Allegation of the Inconcistencies in the Qur’an - Musa, Muhammad Arif; Azmi, Ahmad Sanusi; Mohamed Yusoff, Adnan (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
The study aims to analyse ‘Abd al-Masīh al-Kindi’s (9th century) and John of Damascus’s (7th century) argumentation on the alleged inconsistencies in the Qur’an. The study is a qualitative study employing textual analysis method. It analyses William Muir’s translation of al-Kindi’s apology to ‘Abd Allah al-Hāshimī which was written in the court of al-Ma’mūn and John of Damascus’s writings on Islam in The Heresy of Ishmaelites which was compiled in the The Fount of Knowledge. The study investigates the alleged inconsistencies in the Qur’an which were addressed by the two scholars. The study concludes that alleged inconsistencies in the Qur’an stands as the one of the major arguments for early critics of the Qur’an among Christian apologetics. They cited the assumed contradictory verses in the Qur’an and present them in a polemical manner with the intention to vilify the foundation of Islam.